Low-alkali high-adhesion two-component water-based tile back adhesive and preparation process thereof
Patent Information
- Application Number
- CN202611028628.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-23
AI Technical Summary
现有水泥基或普通乳液型背胶在长期潮湿或浸水环境下,容易发生水化产物迁移及界面结构破坏,导致粘结强度显著下降,进而引发空鼓、脱落等工程质量问题;由于水泥体系中碱性物质(如氢氧化钙)在水化过程中易向材料表面迁移并析出,在瓷砖背面或接触界面形成白色结晶或泛碱现象,不仅影响装饰效果,还可能进一步削弱界面粘结性能
1、本发明通过构建丙烯酸乳液与可再分散乳胶粉协同作用形成的有机-无机互穿网络结构,并与水泥水化产物共同形成致密复合膜层,使界面结构更加连续稳定,从而显著提高瓷砖背胶在常温及长期服役条件下的整体粘结强度与结构完整性。
Smart Images

Figure CN122958121A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building decoration materials technology, specifically low alkali and high adhesion two-component water-based ceramic tile back adhesive and its preparation process. Background Technology
[0002] With the development of the building decoration industry, high-end decorative materials such as large-format ceramic tiles, sintered stone slabs, and antique-style tiles are widely used in indoor and outdoor projects, placing higher demands on the bonding performance, water resistance, and long-term stability of the tiling materials. Traditional tile tiling materials mainly include cement-based tile adhesive or single-component water-based tile backing adhesive, but the following problems still exist in actual use: Existing cement-based or ordinary emulsion-type adhesives are prone to migration of hydration products and damage to the interface structure in long-term humid or water-immersed environments, resulting in a significant decrease in bonding strength and causing engineering quality problems such as hollowing and detachment. Because alkaline substances (such as calcium hydroxide) in the cement system are prone to migrate to the material surface and precipitate during the hydration process, white crystals or efflorescence are formed on the back of the tile or at the contact interface, which not only affects the decorative effect but may also further weaken the interfacial bonding performance.
[0003] Furthermore, traditional single-component or simple compound adhesives are mainly based on fillers or simple polymer film formation in their structural design, lacking a synergistic structural design between organic and inorganic phases. This makes it difficult to maintain long-term stable interfacial bonding performance under conditions of immersion in water or changes in temperature and humidity. Existing materials are quite sensitive to the water ratio and construction environment during construction. If too much water is added on site or if an effective surface-drying film structure is not formed after coating, it is easy to lay the adhesive directly without forming a film at the interface, thereby further reducing the reliability of the bond.
[0004] Therefore, there is an urgent need to develop a two-component water-based ceramic tile adhesive system that can form a stable interface protective layer on the basis of an organic-inorganic synergistic structure, while also possessing low alkali efflorescence performance, high bonding strength, and good water resistance stability, in order to meet the usage requirements of modern high-standard ceramic tile and slab paving projects. Summary of the Invention
[0005] The purpose of this invention is to provide a low-alkali, high-adhesion two-component water-based ceramic tile back adhesive and its preparation process, so as to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a low-alkali, high-adhesion two-component water-based ceramic tile back adhesive, comprising a component A, an aqueous organic emulsion system, and a component B, an inorganic dry powder system, which are mixed in a mass ratio of component A: component B = 1:1 to form a composite adhesive material.
[0007] Component A includes hydrolysis-resistant pure acrylic emulsion, deionized water, and an additive system including wetting and penetrating agents, silicone defoamers, polyurethane associative thickeners, dispersants, preservatives, and pH adjusters.
[0008] Component B includes low-alkali silicate cement, ultrafine quartz sand, heavy calcium carbonate powder, hydroxypropyl methylcellulose ether, redispersible latex powder, polycarboxylate superplasticizer powder, and organosilicon hydrophobic powder.
[0009] During the system construction process, the acrylic emulsion in component A and the redispersible latex powder in component B form an organic-inorganic synergistic interpenetrating network structure under the synergistic effect of hydration and film formation, and together with the cement hydration products, they construct a continuous and dense composite film structure. At the same time, the organosilicon hydrophobic powder migrates and accumulates in the interface region, forming a hydrophobic barrier layer. This hydrophobic barrier layer and the composite film together constitute a dual-interface protection structure, thereby effectively blocking the migration path of calcium hydroxide to the interface during the cement hydration process.
[0010] This invention also provides a preparation process for a low-alkali, high-adhesion two-component water-based ceramic tile backing adhesive, comprising the following steps: First, mix component A and component B in the specified proportions and stir thoroughly to form a uniform adhesive system. Then, allow it to mature for a short time at 20℃~28℃ to stabilize the system structure. Next, apply the adhesive evenly to the back of the tile while controlling the thickness. Then, let it stand under natural conditions to form a surface-drying film structure. Finally, carry out the tiling construction to form a stable and dense composite adhesive layer at the interface.
[0011] By controlling the surface drying film-forming process, the interface structure is pre-cured and shaped before application, thereby improving the bonding stability and alkali resistance in water immersion environments.
[0012] The beneficial effects of this invention are as follows: 1. This invention constructs an organic-inorganic interpenetrating network structure formed by the synergistic effect of acrylic emulsion and redispersible latex powder, and forms a dense composite film layer together with cement hydration products, making the interface structure more continuous and stable, thereby significantly improving the overall bonding strength and structural integrity of tile back adhesive under normal temperature and long-term service conditions.
[0013] 2. This invention introduces organosilicon hydrophobic powder into the system and forms a hydrophobic enrichment layer in the interface region during the hydration process. Together with the composite film layer, it forms a dual-interface protection structure, thereby effectively blocking the migration path of calcium hydroxide to the interface, significantly reducing efflorescence and whitening phenomena, and improving the long-term appearance stability of the decorative layer.
[0014] 3. By setting a surface-drying film-forming construction process, the present invention enables the adhesive system to form a stable and dense interface structure before laying, avoiding structural damage caused by direct laying in a wet state. This significantly improves the adhesion retention rate and durability under water immersion and freeze-thaw cycle conditions, and enhances construction tolerance and engineering adaptability. Attached Figure Description
[0015] Figure 1 This is a flowchart of the preparation process of the present invention; Figure 2 This is a flowchart of component A and its preparation process in this invention; Figure 3 This is a flowchart of component B of the present invention and its preparation process. Detailed Implementation
[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1: like Figure 1-3 As shown, this embodiment provides a low-alkali, high-adhesion two-component water-based tile back adhesive, comprising component A and component B, which are mixed in a mass ratio of 1:1 for use. Preparation of Component A: Component A is prepared by weighing 680 parts of hydrolysis-resistant pure acrylic emulsion, 220 parts of deionized water, 3 parts of wetting and penetrating agent, 2 parts of silicone defoamer, 4 parts of polyurethane associative thickener, 4 parts of dispersant, 1 part of preservative and 3 parts of pH adjuster according to the mass ratio. In the preparation process, firstly, metered deionized water is added to the reaction vessel, and then dispersant and pH adjuster are added sequentially under continuous stirring to ensure complete and uniform dissolution. Subsequently, hydrolysis-resistant pure acrylic emulsion is slowly added, and the stability of the system is controlled during stirring to avoid demulsification. After the emulsion is mixed evenly, wetting and penetrating agent, silicone defoamer and preservative are added sequentially to ensure that each additive is fully dispersed in the system. Finally, polyurethane associative thickener is added to adjust the rheological properties of the system. After the system reaches a uniform and stable state, stirring is continued for a certain period of time, and after standing to remove bubbles, component A is obtained.
[0018] Preparation of Component B: Component B is prepared by weighing 400 parts of low-alkali silicate cement, 360 parts of ultrafine quartz sand, 160 parts of heavy calcium carbonate powder, 3 parts of hydroxypropyl methylcellulose ether, 28 parts of redispersible latex powder, 2 parts of polycarboxylate superplasticizer powder and 1 part of organosilicon water-repellent powder according to the mass ratio. In the preparation process, cement, ultrafine quartz sand, and heavy calcium carbonate powder are first added to a mixing device for initial uniform mixing to achieve a uniform dispersion of the inorganic aggregates. Then, hydroxypropyl methylcellulose ether, redispersible latex powder, and polycarboxylate superplasticizer powder are added and mixing continues to ensure the functional powders are evenly distributed within the inorganic matrix. Finally, organosilicon hydrophobic powder is added for a second mixing process to fully disperse it in the system. After mixing, the powders are sieved to ensure particle size uniformity, ultimately yielding component B.
[0019] Construction method: During construction, mix component A and component B in a 1:1 mass ratio and mechanically stir to form a uniform adhesive system. After mixing, let the adhesive stand for a certain period of time at an environment with a temperature of 20℃ to 28℃ to allow the internal structure of the system to stabilize. Then, evenly apply the adhesive to the back of the tile, controlling the coating thickness between 0.8 mm and 1.2 mm. After application, let it stand under natural conditions for a period of time to form a surface-dry film structure before proceeding with the tile laying construction.
[0020] Example 2: Based on Example 1, component A was prepared as follows: 700 parts of hydrolysis-resistant pure acrylic emulsion, 220 parts of deionized water, 3 parts of wetting and penetrating agent, 2 parts of silicone defoamer, 4 parts of polyurethane associative thickener, 4 parts of dispersant, 1 part of preservative and 3 parts of pH adjuster were weighed according to the following mass ratio. In the preparation process, firstly, metered deionized water is added to the reaction vessel, and then dispersant and pH adjuster are added sequentially under continuous stirring to ensure complete and uniform dissolution. Subsequently, hydrolysis-resistant pure acrylic emulsion is slowly added, and the stability of the system is controlled during stirring to avoid demulsification. After the emulsion is mixed evenly, wetting and penetrating agent, silicone defoamer and preservative are added sequentially to ensure that each additive is fully dispersed in the system. Finally, polyurethane associative thickener is added to adjust the rheological properties of the system. After the system reaches a uniform and stable state, stirring is continued for a certain period of time, and after standing to remove bubbles, component A is obtained.
[0021] Preparation of Component B: Component B is prepared by weighing 400 parts of low-alkali silicate cement, 360 parts of ultrafine quartz sand, 160 parts of heavy calcium carbonate powder, 3 parts of hydroxypropyl methylcellulose ether, 30 parts of redispersible latex powder, 2 parts of polycarboxylate superplasticizer powder and 1 part of organosilicon water-repellent powder according to the mass ratio. In the preparation process, cement, ultrafine quartz sand, and heavy calcium carbonate powder are first added to a mixing device for initial uniform mixing to achieve a uniform dispersion of the inorganic aggregates. Then, hydroxypropyl methylcellulose ether, redispersible latex powder, and polycarboxylate superplasticizer powder are added and mixing continues to ensure the functional powders are evenly distributed within the inorganic matrix. Finally, organosilicon hydrophobic powder is added for a second mixing process to fully disperse it in the system. After mixing, the powders are sieved to ensure particle size uniformity, ultimately yielding component B.
[0022] Construction method: During construction, mix component A and component B in a 1:1 mass ratio and mechanically stir to form a uniform adhesive system. After mixing, let the adhesive stand for a certain period of time at an environment with a temperature of 20℃ to 28℃ to allow the internal structure of the system to stabilize. Then, evenly apply the adhesive to the back of the tile, controlling the coating thickness between 0.8 mm and 1.2 mm. After application, let it stand under natural conditions for a period of time to form a surface-dry film structure before proceeding with the tile laying construction.
[0023] Example 3: Based on Example 1, component A was prepared as follows: 680 parts of hydrolysis-resistant pure acrylic emulsion, 220 parts of deionized water, 3 parts of wetting and penetrating agent, 2 parts of silicone defoamer, 4 parts of polyurethane associative thickener, 4 parts of dispersant, 1 part of preservative and 3 parts of pH adjuster were weighed according to the following mass ratio. In the preparation process, firstly, metered deionized water is added to the reaction vessel, and then dispersant and pH adjuster are added sequentially under continuous stirring to ensure complete and uniform dissolution. Subsequently, hydrolysis-resistant pure acrylic emulsion is slowly added, and the stability of the system is controlled during stirring to avoid demulsification. After the emulsion is mixed evenly, wetting and penetrating agent, silicone defoamer and preservative are added sequentially to ensure that each additive is fully dispersed in the system. Finally, polyurethane associative thickener is added to adjust the rheological properties of the system. After the system reaches a uniform and stable state, stirring is continued for a certain period of time, and after standing to remove bubbles, component A is obtained.
[0024] Preparation of Component B: Component B is prepared by weighing 400 parts of low-alkali silicate cement, 360 parts of ultrafine quartz sand, 160 parts of heavy calcium carbonate powder, 3 parts of hydroxypropyl methylcellulose ether, 28 parts of redispersible latex powder, 2 parts of polycarboxylate superplasticizer powder and 2 parts of organosilicon water-repellent powder according to the mass ratio. In the preparation process, cement, ultrafine quartz sand, and heavy calcium carbonate powder are first added to a mixing device for initial uniform mixing to achieve a uniform dispersion of inorganic aggregates. Then, hydroxypropyl methylcellulose ether, redispersible latex powder, and polycarboxylate superplasticizer powder are added and mixed further to ensure that the functional powders are evenly distributed in the inorganic matrix. Finally, organosilicon hydrophobic powder is added for secondary mixing to fully disperse it in the system. After mixing, the powder is sieved to ensure uniform particle size, and finally, component B is obtained.
[0025] Construction Method: During construction, mix component A and component B in a 1:1 mass ratio and mechanically stir to form a homogeneous adhesive system. Allow the mixed adhesive to stand at an environment of 20℃ to 28℃ for a certain period to mature and stabilize the internal structure. Then, evenly apply the adhesive to the back of the tile, controlling the coating thickness between 0.8 mm and 1.2 mm. After application, allow it to stand naturally for a period to form a surface-dry film before proceeding with tile installation.
[0026] Comparative Example 1: Preparation of Component A: Component A is prepared by weighing 680 parts of hydrolysis-resistant pure acrylic emulsion, 220 parts of deionized water, 3 parts of wetting and penetrating agent, 2 parts of silicone defoamer, 4 parts of polyurethane associative thickener, 4 parts of dispersant, 1 part of preservative and 3 parts of pH adjuster according to the mass ratio. In the preparation process, firstly, metered deionized water is added to the reaction vessel, and then dispersant and pH adjuster are added sequentially under continuous stirring to ensure complete and uniform dissolution. Subsequently, hydrolysis-resistant pure acrylic emulsion is slowly added, and the stability of the system is controlled during stirring to avoid demulsification. After the emulsion is mixed evenly, wetting and penetrating agent, silicone defoamer and preservative are added sequentially to ensure that each additive is fully dispersed in the system. Finally, polyurethane associative thickener is added to adjust the rheological properties of the system. After the system reaches a uniform and stable state, stirring is continued for a certain period of time, and after standing to remove bubbles, component A is obtained.
[0027] Preparation of Component B: Component B is prepared by weighing 400 parts of low-alkali silicate cement, 360 parts of ultrafine quartz sand, 160 parts of heavy calcium carbonate powder, 3 parts of hydroxypropyl methylcellulose ether, 28 parts of redispersible latex powder, and 2 parts of polycarboxylate superplasticizer powder according to the mass ratio. In the preparation process, cement, ultrafine quartz sand, and heavy calcium carbonate powder are first added to a mixing device for initial uniform mixing to achieve a uniform dispersion of inorganic aggregates. Then, hydroxypropyl methylcellulose ether, redispersible latex powder, and polycarboxylate superplasticizer powder are added and mixed further to ensure that the functional powders are evenly distributed in the inorganic matrix. Finally, organosilicon hydrophobic powder is added for secondary mixing to fully disperse it in the system. After mixing, the powder is sieved to ensure uniform particle size, and finally, component B is obtained.
[0028] Construction method: During construction, mix component A and component B in a 1:1 mass ratio and mechanically stir to form a uniform adhesive system. After mixing, let the adhesive stand for a certain period of time at an environment with a temperature of 20℃ to 28℃ to allow the internal structure of the system to stabilize. Then, evenly apply the adhesive to the back of the tile, controlling the coating thickness between 0.8 mm and 1.2 mm. After application, let it stand under natural conditions for a period of time to form a surface-dry film structure before proceeding with the tile laying construction.
[0029] Comparative Example 2: Preparation of Component A: Component A is prepared by weighing 680 parts of hydrolysis-resistant pure acrylic emulsion, 220 parts of deionized water, 3 parts of wetting and penetrating agent, 2 parts of silicone defoamer, 4 parts of polyurethane associative thickener, 4 parts of dispersant, 1 part of preservative and 3 parts of pH adjuster according to the mass ratio. In the preparation process, metered deionized water is first added to the reaction vessel. Dispersant and pH adjuster are added sequentially under continuous stirring to ensure they are fully dissolved and homogeneous. Then, ordinary EVA emulsion is slowly added, and the stability of the system is controlled during stirring to avoid demulsification. After the emulsion is mixed evenly, wetting and penetrating agent, silicone defoamer and preservative are added sequentially to ensure that each additive is fully dispersed in the system. Finally, polyurethane associative thickener is added to adjust the rheological properties of the system. After the system reaches a homogeneous and stable state, stirring is continued for a certain period of time, and after standing to remove bubbles, component A is obtained.
[0030] Preparation of Component B: Component B is prepared by weighing 400 parts of low-alkali silicate cement, 360 parts of ultrafine quartz sand, 160 parts of heavy calcium carbonate powder, 3 parts of hydroxypropyl methylcellulose ether, 2 parts of polycarboxylate superplasticizer powder and 1 part of organosilicon water-repellent powder according to the mass ratio. In the preparation process, cement, ultrafine quartz sand, and heavy calcium carbonate powder are first added to a mixing device for initial uniform mixing to achieve a uniform dispersion of the inorganic aggregates. Then, hydroxypropyl methylcellulose ether, redispersible latex powder, and polycarboxylate superplasticizer powder are added and mixing continues to ensure the functional powders are evenly distributed within the inorganic matrix. Finally, organosilicon hydrophobic powder is added for a second mixing process to fully disperse it in the system. After mixing, the powders are sieved to ensure particle size uniformity, ultimately yielding component B.
[0031] Construction method: During construction, mix component A and component B in a 1:1 mass ratio and mechanically stir to form a uniform adhesive system. After mixing, let the adhesive stand for a certain period of time at an environment with a temperature of 20℃ to 28℃ to allow the internal structure of the system to stabilize. Then, evenly apply the adhesive to the back of the tile, controlling the coating thickness between 0.8 mm and 1.2 mm. After application, let it stand under natural conditions for a period of time to form a surface-dry film structure before proceeding with the tile laying construction.
[0032] Comparative Example 3: Preparation of Component A: Component A is prepared by weighing 680 parts of hydrolysis-resistant pure acrylic emulsion, 220 parts of deionized water, 3 parts of wetting and penetrating agent, 2 parts of silicone defoamer, 4 parts of polyurethane associative thickener, 4 parts of dispersant, 1 part of preservative and 3 parts of pH adjuster according to the mass ratio. In the preparation process, metered deionized water is first added to a reaction vessel. Dispersant and pH adjuster are added sequentially under continuous stirring to ensure complete and uniform dissolution. Then, hydrolysis-resistant pure acrylic emulsion is slowly added, and the system stability is controlled during stirring to avoid demulsification. After the emulsion is mixed evenly, wetting and penetrating agent, silicone defoamer and preservative are added sequentially to ensure that each additive is fully dispersed in the system. Finally, polyurethane associative thickener is added to adjust the rheological properties of the system. After the system reaches a uniform and stable state, stirring is continued for a certain period of time, and after standing to remove bubbles, component A is obtained.
[0033] Preparation of Component B: Component B is prepared by weighing 400 parts of low-alkali silicate cement, 360 parts of ultrafine quartz sand, 160 parts of heavy calcium carbonate powder, 3 parts of hydroxypropyl methylcellulose ether, 28 parts of redispersible latex powder, 2 parts of polycarboxylate superplasticizer powder and 1 part of organosilicon water-repellent powder according to the mass ratio. In the preparation process, cement, ultrafine quartz sand, and heavy calcium carbonate powder are first added to a mixing device for initial uniform mixing to achieve a uniform dispersion of the inorganic aggregates. Then, hydroxypropyl methylcellulose ether, redispersible latex powder, and polycarboxylate superplasticizer powder are added and mixing continues to ensure the functional powders are evenly distributed within the inorganic matrix. Finally, organosilicon hydrophobic powder is added for a second mixing process to fully disperse it in the system. After mixing, the powders are sieved to ensure particle size uniformity, ultimately yielding component B.
[0034] Construction method: During construction, mix components A and B in a 1:1 mass ratio and mechanically stir to form a uniform adhesive system. After mixing, let the adhesive stand for a certain period of time at an environment with a temperature of 20℃ to 28℃ to allow the internal structure of the system to stabilize. Then, apply the adhesive evenly to the back of the tile, controlling the coating thickness between 0.8 mm and 1.2 mm. After the coating is completed, proceed with the tile laying construction.
[0035] The performance tests of this invention were conducted in a standard experimental environment, with the ambient temperature controlled at 23℃ and the relative humidity controlled at 50% and 5%, and the sample curing time was 28 days. Tensile bond strength was determined according to the relevant test methods for building adhesives. After the prepared sample was cured on a standard substrate, it was subjected to tensile testing by a universal testing machine, and its maximum breaking strength was recorded, expressed in megapascals. The water immersion bond strength test method is to completely immerse the standard cured sample in room temperature water for seven days, remove it and allow it to recover under standard conditions for a certain period of time, and then measure it according to the tensile bond strength test method. The efflorescence level is determined by visual evaluation and is divided into three levels according to the degree of surface whitening: level 0 indicates no obvious efflorescence, level 1 indicates slight efflorescence, level 2 indicates obvious efflorescence, and level 3 indicates severe efflorescence. The freeze-thaw cycle test method involves placing the sample in a freeze-thaw cycle environment for five cycles. Each cycle includes a low-temperature freezing process and a room-temperature thawing process. After the cycle is completed, the bond strength retention rate is tested and expressed as a percentage. Test results comparison table: Comparison of adhesion performance, efflorescence performance, and durability: sample Strength at room temperature (MPa) 7 days of immersion in water (MPa) alkali grade Adhesion retention rate after freeze-thaw cycles Example 1 1.05 0.68 0 88% Example 2 1.12 0.72 0 92% Example 3 1.03 0.76 0 90% Comparative Example 1 0.92 0.52 2 73% Comparative Example 2 0.78 0.41 3 65% Comparative Example 3 0.81 0.38 3 60% The examples are all significantly better than the comparative examples, indicating that the structure of the present invention has a stable bonding and reinforcing effect; Comparative Example 2 showed the most significant performance degradation, proving that the organic-inorganic interpenetrating network structure is the core source of bonding performance. Comparative Example 1 showed significant alkali blooming, indicating that the organosilicon hydrophobic powder plays a key role in inhibiting alkali migration; Comparative Example 3 showed severe failure, indicating that the surface drying film formation process is necessary for the formation of the interface structure; Freeze-thaw cycle results show that the present invention has good environmental adaptability and long-term stability; This invention utilizes the synergistic effect of acrylic emulsion and redispersible latex powder to form an organic-inorganic interpenetrating network structure, which together with cement hydration products to construct a dense composite film. At the same time, the organosilicon hydrophobic powder forms a hydrophobic barrier layer at the interface, thereby blocking the migration path of calcium hydroxide in the hydration products, reducing the risk of efflorescence, and improving the long-term stability of the interface.
[0036] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "include," "contain," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus.
[0037] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A low-alkali, high-adhesion two-component water-based ceramic tile adhesive, characterized in that: It includes component A, an aqueous organic emulsion system, and component B, an inorganic dry powder system. When used, the components A and B are mixed in a mass ratio of 1:1 to form a composite adhesive material. in: Component A includes hydrolysis-resistant pure acrylic emulsion, deionized water, wetting and penetrating agent, silicone defoamer, polyurethane associative thickener, dispersant, preservative and pH adjuster; Component B includes low-alkali silicate cement, ultrafine quartz sand, heavy calcium carbonate powder, hydroxypropyl methylcellulose ether, redispersible latex powder, polycarboxylate superplasticizer powder, and organosilicon water-repellent powder; During the hydration and film formation process, the acrylic emulsion in component A and the redispersible latex powder in component B form an organic-inorganic synergistic interpenetrating network structure, which together with the inorganic skeleton generated by cement hydration constitutes a continuous and dense composite film layer. The organosilicon hydrophobic powder forms a hydrophobic enrichment layer in the interface region, which together with the composite film layer constitutes a dual-interface protection structure, thereby blocking the migration path of calcium hydroxide to the interface and achieving the effect of reducing efflorescence.
2. The low-alkali, high-adhesion two-component water-based ceramic tile adhesive according to claim 1, characterized in that: The alkali content of the low-alkali silicate cement is 0.6% (calculated as Na2O).
3. The low-alkali, high-adhesion two-component water-based ceramic tile adhesive according to claim 1, characterized in that: The redispersible latex powder is a latex powder co-modified with EVA and acrylic acid.
4. The low-alkali, high-adhesion two-component water-based ceramic tile adhesive according to claim 1, characterized in that: The polyurethane associative thickener is used to form a shear-thinning structure, which reduces the viscosity of the system under construction shear and restores high viscosity under static conditions.
5. The low-alkali, high-adhesion two-component water-based ceramic tile adhesive according to claim 1, characterized in that: The organosilicon hydrophobic powder is used to migrate to the interface during hydration and form a hydrophobic barrier layer.
6. The low-alkali, high-adhesion two-component water-based ceramic tile adhesive according to claim 1, characterized in that: The composite adhesive material has a bonding strength of 0.6 MPa after being immersed in water at room temperature for 7 days.
7. The low-alkali, high-adhesion two-component water-based ceramic tile adhesive according to claim 1, characterized in that: The composite adhesive material has a tensile bond strength of 1.0 MPa at room temperature.
8. A preparation process for a low-alkali, high-adhesion two-component water-based ceramic tile back adhesive, characterized in that, Includes the following steps: S1. Mix and stir components A and B at a mass ratio of 1:1 to form an adhesive system; S2. Let it stand and mature at 20℃~28℃ for 2~5 minutes; S3. Apply the mixture evenly to the back of the tile, with a coating thickness of 0.8–1.2 mm; S4. After the surface-dry film layer is formed by standing at room temperature for 10-20 minutes, the paving construction can proceed. Among them, a stable interface structure is formed through the surface drying film formation process to improve the adhesion stability and anti-alkali efflorescence performance under water immersion conditions.
9. The preparation process of the low-alkali, high-adhesion two-component water-based ceramic tile back adhesive according to claim 8, characterized in that: No additional water should be added for dilution during construction.
10. The preparation process of the low-alkali, high-adhesion two-component water-based ceramic tile back adhesive according to claim 8, characterized in that: The surface drying film-forming step is used to form a continuous and dense waterproof interface layer to prevent direct wet application from causing blistering or adhesion failure.